Development of a Web Based Electronic Procurement System - Muchiri, Philip Rajab; Bosire, Zakary O.; Kemei, Peter (My University, 2015)
A well-functioning procurement system is an essential requirement for a developing country like Kenya. In order to promote development, proper management of scarce resources is vital. A system that ensures transparency, efficiency, cost effectiveness, easy to control and monitor can accelerate development to great heights. It will encourage fair competition and freedom of information amongst trading partners in a regional block. This can be achieved by using an electronic government procurement system realized as a web based internet portal. This paper explores the design methodology applicable to the design and implementation of an electronic Government Procurement System (e-GP). The paper further shows how Object Oriented technology can be applied to model the business artifacts of the system through the Unified Modeling Language (UML). The internet provides a lot of information through the web that makes better decisions to be made quickly.
Keywords: E-Procurement; UML; Web Application Portal